2024
DOI: 10.1021/acsanm.3c05615
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Based Nanoparticles as Antimicrobial Agents: A Review

Li Luo,
Wan Huang,
Jun Zhang
et al.

Abstract: Antibiotic abuse has become a rising public health concern in recent years, leading to dangerous bacteria developing antibiotic resistance to most antibiotic medicines currently in use. Traditional antimicrobial medications have been helpful in the early stages of treating numerous forms of serious bacterial infectious diseases; however, despite the significant therapeutic benefit, there are a number of issues with follow-up treatment. Metalbased nanomaterials, which have properties including the difficulty of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 223 publications
0
2
0
Order By: Relevance
“…The increasing bacterial resistance to antibiotics represents a significant global health challenge, underscoring the urgent need to develop novel and potent agents capable of treating a diverse range of microorganisms and effectively combating the escalating bacterial resistance. Metal-based nanomaterials, specifically noble metal NPs, have demonstrated considerable potential as antimicrobial agents due to their intrinsic antibacterial activities [ 75 , 76 , 77 , 78 ]. Therefore, substantial research interest has been focused on the development of Ag and AuNPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing bacterial resistance to antibiotics represents a significant global health challenge, underscoring the urgent need to develop novel and potent agents capable of treating a diverse range of microorganisms and effectively combating the escalating bacterial resistance. Metal-based nanomaterials, specifically noble metal NPs, have demonstrated considerable potential as antimicrobial agents due to their intrinsic antibacterial activities [ 75 , 76 , 77 , 78 ]. Therefore, substantial research interest has been focused on the development of Ag and AuNPs.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have indicated that the size of nanomaterials plays a crucial role in bactericidal activity. Small nanoparticles (2–10 nm) are known to cause more membrane damage than larger ones due to their increased surface area contact with bacterial cells [ 78 , 79 ]. The diminished toxicity of the NPs@AL against E. coli can be ascribed to the diversity in cell wall composition between Gram-positive and Gram-negative bacteria.…”
Section: Resultsmentioning
confidence: 99%